3D ultrasound imaging by synthetic transmit aperture beamforming using a spherically curved array transducer. (1st July 2022) - Hayashi, Eiki; Kanno, Naoya; Shintate, Ryo; Ishii, Takuro; Nagaoka, Ryo; Saijo, Yoshifumi
Abstract: Visualization of dermal circulation is important in the field of skin healthcare. We have developed a three-dimensional (3D) photoacoustic (PA) imaging system using a spherically curved array transducer that can visualize the microscale circulation in the skin layers, but limited anatomical information was available around the microvasculature. To provide such anatomical information, this study was aimed at devising a high-quality and high-speed ultrasound (US) imaging framework, particularly, for the spherical array transducer. We tested three synthetic transmit aperture (STA) methods, all-elements, outer-track, and inner-track, for transmission by evaluating the spatial resolution and uniformity of 3D images of point and copper-wire targets. The results demonstrated that the all-elements and outer-track STA methods could provide uniform and clear 3D images. In addition, the outer-track STA could be performed with fewer transmissions than the all-elements STA, and it will be useful for realizing real-time, high-resolution 3D PA/US imaging.